Atmospheric Nitrogen Plasma-Induced for Embedding NH2@Cubic-Bicontinuous Mesoporous Silica as Uranium (VI) Adsorbent Candidate in Seawater - Pamungkas, N. S.; Wongsawaeng, D.; Swantomo, D.; Kamonsuangkasem, K.; Chio-Srichan, S. (National Research and Innovation Agency, 2024)
This work aims to achieve interesting progress in uranium extraction by introducing a promising strategy that utilizes atmospheric nitrogen plasma-induced amine modification of CBC (Cubic Bi-continuous) material, providing a compelling pathway to enhance CBC's adsorption properties specifically for uranium harvesting. CBCs mesoporous silica samples were prepared by mixing the Pluronic F-127 as a template and TEOS (Tetraethyl Orthosilicate) as silica sources in the sol-gel process under acidic conditions. The obtained CBCs were treated using nitrogen plasma at room temperature (RT) under atmospheric pressure in a customized-borosilicate plasma reactor. Subsequently, the treated CBSs were grafted with amine groups. The final samples were characterized using SAXS (Small Angle Synchrotron X-ray Scattering) to determine the phase and structure, SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy) analysis to quantify the presence of silica, oxygen, and embedded nitrogen, and Specific Surface Area (SSA) Analyzer using Brunauer-Emmett-Teller (BET) method to determine the specific surface area and pore size distribution. The SAXS profiles indicate that the obtained samples can be classified as CBCs Im3m mesoporous silica. The presence of silica, oxygen, and nitrogen was verified through SEM-EDS analysis, with approximate compositions of 36-37 %, 51-62 %, and 0.7-1.0 %, respectively. The use of SSA analysis further supported the findings, confirming the typical adsorption isotherm IV model. The specific surface areas were measured to be 371 m2/g for pure CBC, 573 m2/g for P1-CBC, and 607 m2/g for P2-CBC. The pore size distribution analysis revealed mesoporous characteristics within the material, with pore sizes ranging from 4 to 6.5 nm. On a batch laboratory scale, the material achieved the highest adsorption capacity of 15.68 mg-U(VI)/g-NH2@P1-CBC from natural seawater after 1 hour of contact time.